BENTUK PERTUNJUKAN KESENIAN TIBAN DI DESA SURAT KECAMATAN MOJO KABUPATEN KEDIRI - Hayya, Fina Lu'lual; Slamet, Slamet (Greget: Jurnal Kreativitas dan Studi Tari, 2023)
Tiban Performing art at Desa Surat Kecamatan Mojo Kabupaten Kediri is a research that discusses the form and activity of art in the community.This research aims to explore the form of performance found in the Tiban arts in Surat Village, Mojo District, Kediri Regency. The problems to be discussed are: (1) How is Arriving in Surat Village, Mojo District, Kediri Regency? (2) How is the form of the Tiban show in Surat Village, Mojo District, Kediri Regency? Problems regarding the Tiban were analyzed using Richard Schechner's theory. This study used a qualitative research method, with an ethnoarchaeological approach. Ethnochoreology is one of the branches of science that discusses ethnicity and its various problems. Answering about Tiban in Sur at Village uses Talcott Parsons' theory which explains constitutive, cognitive, moral values, and also expressions, while regarding the form of Tiban uses Richard Schechner's theory which focuses on performance studies. The collection of data and information is carried out by means of observation or observation of research objects, interviews, and library research. The results of this study indicate that the art of Tiban cannot be separated from public trust, knowledge, moral values, and expressions that are embodied in Tiban in Surat Village, Mojo District, Kediri Regency. The form of performance is human activity in the form of Tiban performances which are manifested into games, rituals, and business, as well as the audience that exists as a series of human activities in the form of Tiban art performances.